Efficacy and Safety of Teneligliptin in Patients of Type 2 Diabetes Mellitus with Chronic Kidney Disease: ATEND-CKD Study - Kiran, Dr. Mayuresh Dilip; Vakharia, Dr. Monali; Pawaskar, Lalit Jeevan; Sheikh, Shaheen Naseem (International Journal of Innovative Research in Medical Science, 2019)
Background: Prior studies have estimated prevalence of CKD among non-institutionalized adults with type 2 diabetes mellitus (T2DM) at 34.5–42.3%, with most CKD cases identified as early stage (stage 1 or 2). Diabetes affects many organs, and complications due to high blood glucose are an important cause of disability, reduced quality of life, and premature death. (8) There is paucity of data regarding efficacy and safety of teneligliptin in T2DM with chronic kidney disease (CKD) especially in Indian population and therefore this study was planned. Methods: This was a phase IV, multi-centric, open labelled, non-comparative, user initiated study done in 405 patients diagnosed with CKD due to uncontrolled T2DM. Patients were given samples of Teneligliptin 20 mg at initial visit at day 1 and asked to take one tablet daily for a total of 90 days. Glycemic and renal profile during initial and follow up visit was used for efficacy evaluation. Patients were instructed to keep a diary to record daily symptoms and adverse events if any for safety evaluation. Results: Teneligliptin reported significant mean reduction in FPG and PPBG by 40.4 and 57.5 mg/dl respectively. At 12 weeks, statistically significant 0.9% reduction in HbA1c was noted. Effects on renal parameters were also found significantly positive in this study, with reduction of Sr. creatinine by around 4% and reduction in the BUN of around 9%. There was decrease in mean urinary albumin and UACR and increase in mean eGFR, though it was not statistically significant. Among all the patients, 6.41% of patients experienced adverse event. Hypoglycemia was the most common adverse event seen in 4.44% of patients followed by constipation (1.23%) and gastritis (0.74%). Conclusion: The study reported significant improvement in glycaemic control, serum creatinine and BUN with teneligliptin.